Appraisal of earnings management across the sectors - Durana, Pavol; Valaskova, Katarina; Siekelova, Anna; Michalkova, Lucia (Journal of Business Economics and Management, 2022)
Financial managers intentionally use the legal manipulation of earnings to the business development. Earnings management is a widespread business finance phenomenon. The approaches and the ways of this practice are marked by many parallels. The main target of the article is to show the clusters with the close approach of the enterprises to the earnings manipulation and demonstrate hidden relations of the earnings management between sectors in the Visegrad Group. The study estimates the earnings management by the Modified Jones model. 52,545 discretionary accruals are computed for Slovak, Czech, Hungarian, and Polish enterprises for 5-year horizon in 19 sectors classified by the NACE. The clusters of close practices of the earnings management are identified based on principal component analysis and cluster analysis in every country of Visegrad Four. Moreover, the results detect the dependences between sectors in the region and the specificity of the sectors.